Odnos medicinskih sester do evtanazije - Kalender Smajlović, Sedina (Obzornik zdravstvene nege, 2022)
Introduction: Euthanasia is a concept that should be discussed from the perspective of medicine, healthcare sciences and social sciences. Nurses form an integral part of healthcare teams, therefore, they should be included in ethical discussions on euthanasia. The aim of the review is to present euthanasia in relation to nursing. Methods: A review of literature in databases COBIB.SI, CIHAHL and PubMed was conducted between November 1, 2020 and December 1, 2020. The search included the following key words: 'euthanasia', 'nursing' in Slovenian, and in English a combination of key words 'attitudes', 'euthanasia', and 'nursing'. The PRISMA flow diagram was used to depict the different phases of the literature review. The quality of sources included in the final analysis was assessed using the hierarchy of evidence. The results were synthesized using thematic analysis. Results: From 138 sources, a total of 21 articles were included in the final analysis. Nurses reported both favorable and unfavorable attitudes towards euthanasia, as well as some ethical dilemmas. A favorable attitude towards euthanasia among nurses was detected in cases of unbearable pain, intense suffering, and terminal illness, while unfavorable attitude was shown in connection to certain demographic and cultural factors of nurses, adherence to compassionate care principles, and respect for the value of human life. Discussion and conclusion: Our findings contribute to understanding nurses' attitudes towards euthanasia and some ethical dilemmas connected to euthanasia. Further comprehensive reviews of ethical dilemmas and moral distress occurring in connection with euthanasia and nursing should be conducted.
Keywords: evtanazija; medicinska etika; zdravstvena nega